Shifting Sugars and Shifting Paradigms - Siegal, Mark L. (PLoS Biol, 2015)
No organism lives in a constant environment. Based on classical studies in molecular biology, many have viewed microbes as following strict rules for shifting their metabolic activities when prevailing conditions change. For example, students learn that the bacterium Escherichia coli makes proteins for digesting lactose only when lactose is available and glucose, a better sugar, is not. However, recent studies, including three PLOS Biology papers examining sugar utilization in the budding yeast Saccharomyces cerevisiae, show that considerable heterogeneity in response to complex environments exists within and between populations. These results join similar recent results in other organisms that suggest that microbial populations anticipate predictable environmental changes and hedge their bets against unpredictable ones. The classical view therefore represents but one special case in a range of evolutionary adaptations to environmental changes that all organisms face.